Increased Anti-Proliferation Performance of NanoChitosan-Moringa Seeds Extract and Co-Treatment with Doxorubicin in Liver Cancer Cells - Susanto, Hendra; Sholeh, Moch; Tri Endharti, Agustina; Nik Malek, Nik Ahmad Nizam; Amaliyah Firdaus, Sa’diyatul Rizqie; Yuda Handaya, Adeodatus; Taufiq, Ahmad (Bogor Agricultural University, Indonesia, 2025)
Hepatocellular carcinoma (HCC) with high epidemiological report data. Pathogenesis in HCC also involves several signaling pathways. This study aims to evaluate the in vitro activity of Moringa seed NanoChitosan against Hep G2 liver cancer cells and Co-Treatment with Doxorubicin. Initially, nanoparticles were prepared by extracting Moringa seeds, formulating them into nano chitosan, and then characterizing the compounds and particle sizes. The IC50 dose was investigated using the MTT assay. Then, the IC50 dose was confirmed in more detail through immunofluorescence, betatrophin gene, several genes in the Wnt-βcatenin-CyclinD1 proliferation pathway, and the addition of the apoptotic effector Caspase-3 using RT-qPCR analysis. Each treatment used a single dose of NCH-Mosee and co-treatment or combination with 4 μg/ml doxorubicin. The IC50 dose was 994 μg/ml in single treatment and 649 μg/ml in combined treatment with Dox. Hep G2 showed a decrease in the expression level of each parameter measured with increasing single dose and combination treatment (p < 0.050). Histologically, cells shrank, betatrophin expression was inhibited, and luminescence was seen, which decreased with increasing dose. In conclusion, NCH-Mosee with dose-tracking toxicity combined with Dox can suppress the viability of Hep G2 cells.